The Association between Serum Cytokine and Chemokine Levels and Antiviral Response by Entecavir Treatment in Chronic Hepatitis B Patients. Issue 3 (April 2018) - Kurihara, Mio; Tsuge, Masataka; Murakami, Eisuke; Mori, Nami; Ohishi, Waka; Uchida, Takuro; Fujino, Hatsue; Nakahara, Takashi; Abe-Chayama, Hiromi; Kawaoka, Tomokazu; Miki, Daiki; Hiramatsu, Akira; et al.
Background: Although nucleoside/nucleotide analogue therapy is thought to suppress chronic hepatitis B (CHB) via regulation of inflammatory cytokines/chemokines, the mechanism is still unclear. In this study, serum cytokine/ chemokine levels were measured in CHB patients treated with entecavir, and the association with antiviral response was analysed. Methods: A total of 78 Japanese patients with CHB were enrolled, and serum cytokine/chemokine levels were measured at baseline and at 12, 24 and 48 weeks of entecavir treatment using the MULTIPLEX kit. Results: Antiviral response to entecavir treatment was significantly associated with hepatitis B surface antigen (HBsAg) titre and serum interferon-gamma-inducible protein 10 (IP-10) level (12w; P =0.0002; OR=0.020 [95% CI 0.002, 0.156], P =0.003; OR=0.042 [95% CI 0.005, 0.336], respectively). HBe-positive patients whose serum macrophage-derived chemokine (MDC) level was lower (<582.83 pg/ml) and IP-10 level was higher (≥1, 323.13 pg/ml) achieved hepatitis B e antigen (HBeAg) loss earlier than those who remained HBeAg-positive ( P =0.044). HBsAg reduction by entecavir treatment was significantly associated with higher initial tumour necrosis factor-alpha (TNF-α) level (≥15.20 pg/ml) and higher alanine aminotransferase level (≥73 IU/l; P =0.009; OR=18.460 [95% CI 2.044, 166.709], P =0.022; OR=7.709 [95% CI 1.341, 44.327], respectively). Conclusions: Results of the present study indicate that changes in cytokine/chemokine levels following entecavir therapy are associated with response to antiviral therapy in CHB patients. Monitoring of serum cytokine/chemokine levels could be useful for predicting reduction of HBV DNA and HBsAg and HBe seroconversion.